Deficiencies in reproductive health counseling in liver transplant recipients. Issue 8 (1st July 2019) - Phillips, Paulina K.; Saha, Sumona; Foley, David P.; Iruretagoyena, Jesus I.; Said, Adnan
Abstract: Background: In liver transplant (LT) recipients of childbearing age, there is often rapid return of fertility post‐transplant. Our aim was to determine whether healthcare providers are documenting reproductive health counseling in LT recipients. Methods: We performed a review of 365 LT recipients (164 female, 201 male) of childbearing age transplanted between 1994 and 2015 at a single center. We evaluated documentation of reproductive health counseling, content of the counseling and its provider. Results: Reproductive health counseling was documented in 7% of LT recipients (14% of females, 0.5% of males). The transplant team provided the counseling in 56%, obstetrics/gynecology in 35%, and primary care in 9%. Twenty‐four post‐LT pregnancies occurred; these were unplanned in 13%. Miscarriage/stillbirth occurred in 7/24 pregnancies (29%). Mycophenolic acid was used by 20% of female recipients at conception. Only age at transplant ( P  = 0.001) and post‐LT pregnancy was associated with documentation of reproductive health counseling in female recipients ( P  = 0.0001). Conclusion: Despite rapid return of fertility in reproductive‐aged LT recipients, documentation of reproductive health counseling in this population is rare in men and women. This increases the potential for adverse maternal and fetal outcomes in this high‐risk population.